Nullity as prerequisite for contract conversion - Mijanović, Dražen (Glasnik Advokatske komore Vojvodine, 2021)
ABSTRACT: Although adopted back in 1978, the conversion (lat. Conversio) is one of the institutes to which no significant attention has been paid in our doctrine. In teaching books that cover the subject of the general part of civil law, and those which serve to teach the law of obligations, this institute is explained laconically – in most cases, apart from the legal definition, we find only the area of application and examples of conversion. We were unable to find monographs on the subject of conversion. On the other hand, in foreign literature, mostly German and Italian, we find a large number of monographs on the topic of conversion. This paper has one part of the norm that prescribes conversion for its subject, and that is the nullity of the contract, which is prescribed as one of conditions for application of conversion. The area of application of the conversion seems to be precisely and clearly defined, especially having in mind the text of the norm and the place of the norm within the Law on obligations, and in the following lines we will see if this is really the case. While searching  for the answer, we also used the comparative method. The area of application of the conversion was considered - and we did not limit ourselves to null contracts, but we also considered the possibility of application to non-existent, avoidable, partially null and partially avoidable contracts, and to valid contracts. Within null contracts, special attention was paid to illegal and immoral ones, and within non-existent ones - to a simulated contract.
Keywords: conversion, nullity, avoidability, relative simulation, requalification.